Analysis of wave propagation for wireless implantable body area network application - N. H. Ramli; Haryati Jaafar; Y. S. Lee; Hazila Othman (Institute of Advanced Engineering and Science, 2019)
The enhancement technologies of wireless body area network improved the health monitoring system. Previous work have been designed the implantable chip printed antenna at 4.8 GHz. This paper is continuing the investigation where the antenna wave propagation in term of attenuation and polarization were studied. The antenna is implanted in human hand voxel model from CST Microwave Studio Software. The performances of the antenna are evaluated in term of return loss, gain and efficiency. Results show that the rate attenuation for the propagation is approximately 0.16 dB up to 0.42 dB. All the results will be guidelines in designing implantable antennas in futures.